2020
DOI: 10.21462/ijefl.v5i1.211
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Features in E-commerce Slogans

Abstract: Slogan is one of the powerful tools to advertise e-commerce products and services. The power of slogan to promote commodities lies primarily on the language style that it employs. This study is aimed at analyzing the linguistic feautures in 38 e-commerce slogans that are popular in Indonesia. The data were analyzed quantitatively and qualitatively. Quantitatively, the data were calculated regarding the frequency of each identified linguistic features: semantic devices, syntactic devices, phonetic devices, orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Similarly, Asyndeton and end rhyme have been repeated five times and ellipsis, repetition and internal rhyme have been repeated equally four times. The repetition of Asyndeton justifies the conclusion of Iswati and Widodo (2020) where Asyndeton comes as the most frequent rhetorical device. Out of nearly 71 percent occupancy of schemes among the total 68 usages of rhetorical devices in this study, only seven devices have captured about 79 percent space among of schemes.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Similarly, Asyndeton and end rhyme have been repeated five times and ellipsis, repetition and internal rhyme have been repeated equally four times. The repetition of Asyndeton justifies the conclusion of Iswati and Widodo (2020) where Asyndeton comes as the most frequent rhetorical device. Out of nearly 71 percent occupancy of schemes among the total 68 usages of rhetorical devices in this study, only seven devices have captured about 79 percent space among of schemes.…”
Section: Discussionmentioning
confidence: 69%
“…One of the highest repetitions of alliteration warrants it. Iswati and Widodo (2020) believe that the strength of sound patterning in any slogan is directly proportional to the height of the brand. Phonetically, the pervasiveness of alliteration is the prevailing evidence in the study of too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work by Nastiti (2013) demonstrated how Charles Sanders Peirce's semiotic and propaganda technique worked their way in Jokowi and Basuki's video clip gubernatorial election campaigns. Last, the current findings in Iswati and Widodo (2020) found that linguistic features in the form of slogans are often acquired in ecommerce products and services.…”
Section: Introductionmentioning
confidence: 56%
“…These pleonasms are just long-winded wordiness like a sentence that includes far more words than is necessary. In the study of Iswati and Widodo (2020), pleonasm is the redundant use of words in a phrase or sentence which deliberately have the same meaning. This device is used on purpose and that is to reinforce meanings.…”
Section: Lexical Devices Used In Crime News Broadcastsmentioning
confidence: 99%